Host specificity testing of Diorhabda carinulata (Coleoptera: Chrysomelidae) as a biological control agent of Tamarix spp. (Tamaricaceae) - Smit, Etienne Rauch (My University, 2017)
Tamarix (Tamaricaceae) is an old world genus of riparian trees, which has been introduced into the USA and South Africa, where it has become invasive. In South Africa, two exotic Tamarix species have become invasive: T. ramosissima Ledeb. and T. chinensis Lour., as well as hybrids of these two species with one another and with the native T. usneoides E Mey. ex Bunge. The initiation of a biological control (biocontrol) programme against Tamarix in South Africa is being considered. To support this effort, the successful biological control programme initiated against Tamarix in the USA was used as a resource. The USA biocontrol programme uses leaf-feeding beetles of the genus Diorhabda (Coleoptera: Chrysomelidae), which defoliate Tamarix trees, leading to the eventual death of the trees after several seasonal defoliation cycles. Diorhabda spp. have therefore been considered for release in South Africa, against the invasive T. ramosissima and T. chinensis. The host specificity of Diorhabda carinulata was tested in open-field multichoice tests as well as laboratory-based choice and no-choice tests using invasive target Tamarix species as well as the indigenous non-target T. usneoides. Open-field host choice tests and outdoor, caged multi-choice tests were conducted in Western Colorado, USA using native and invasive Tamarix material imported from South Africa, identified using molecular genotyping. Sixteen potted Tamarix plants were set out in a Latin Square array at each site, and presence of adults and egg clusters were recorded. Open-field multi-choice trials produced few data, but showed some evidence that D. carinulata preferred the target species. Diorhabda carinulata in outdoor, caged multi-choice trials initially showed preference for invasive target Tamarix species, but readily moved to the native T. usneoides upon removal of the target species from the array. Later outdoor-caged trials found that the beetles alighted and laid eggs on T. usneoides, indicating the possible inclusion of T. usneoides in the host range of the agent. Laboratory paired-choice-trials for both alighting behaviour and oviposition found that adult beetles significantly preferred T. usneoides over T. chinensis, while the beetles did not significantly prefer T. ramosissima or T. usneoides. Laboratory no-choice tests using bouquets found that adults reared on T. usneoides did not significantly differ in weight from those reared on a T. usneoides x T. ramosissima hybrid. No-choice rearing tests found that the egg-to-adult survival rate was significantly higher for D. carinulata individuals reared on T. usneoides than for individuals reared on T. ramosissima. Additionally, the fecundity of females reared from egg to adult on T. usneoides was not significantly different from those reared on T. ramosissima, laying an average of 57.66 ± 13.71 eggs per female, and 32.48 ± 22.35 eggs per female respectively, thus reproductive potential was not reduced on T. usneoides. A climatic suitability model was built using CLIMEX, and included day length induced diapause. The resulting suitability map indicated that no area of South Africa would be suitable for Diorhabda beetles, as the short day length would cause the beetles to remain in diapause for too long, causing their populations to eventually die out as they are unable to reproduce. The evolution of delayed diapause has been observed, therefore southern populations of Diorhabda from the USA may be considered for further study. Diorhabda carinulata will not be a suitable biological control agent against invasive Tamarix in South Africa in light of its ability to readily develop and oviposit on the native T. usneoides, as evidenced by a 233% higher relative suitability for this species over the baseline T. ramosissima, as well as the unsuitability of the South African environment. An alternative biological agent with a higher host specificity and greater environmental suitability should be sought for further research. Keywords: Tamarix, Diorhabda, biological control, host specificity, ecological host range, fundamental host range, climatic compatibility.
A dissertation submitted in partial fulfilment of the requirements for the degree of Master of Science to the Faculty of Science, University of the Witwatersrand, Johannesburg, South Africa 2017.
Keywords: Chrysomelidae; Tamarisks